Quantum-beat analysis of the rotational–vibrational dynamics in D2+ - Winter, M.; Schmidt, R.; Thumm, U. (My University, 2010)
The rapid ionization of D2 in a short and intense laser pulse generates a rotational–vibrational (RV) nuclear wave packet in D2+. By solving the time-dependent Schrödinger equation in full dimensionality, we simulate the coherent evolution of such wave packets and discuss their ro-vibrational dynamics. Within a harmonic time-series analysis of the evolving nuclear probability density, we characterize the RV dynamics in D2+ in an external intense linearly polarized infrared laser field in terms of quantum-beat (QB) spectra in which both internuclear distance and molecular orientation relative to the linearly polarized laser field are resolved. Based on numerical examples for the nuclear dynamics without and under the influence of pulsed and continuum-wave (cw) laser light, we discuss and quantify the signature of RV couplings in QB spectra and the extent to which the QB analysis of measured time-dependent fragment kinetic energy release spectra is expected to image the laser-dressed RV structure of D2+.